PENGARUH MODEL PEMBELAJARAN KOOPERATIF NUMBERED HEAD TOGETHER (NHT) TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA SISWA KELAS V SDN PATOMPO II KECAMATAN MARISO - Nurul Magfirah; Arifin, Jamaluddin; Said, Try Gustaf (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the cooperative learning model of the Numbered Head Together (NHT) type on the learning outcomes of Pancasila Education for fifth-grade students at UPT SPF SDN Patompo II, Mariso District. This research uses a quantitative approach with a pre-experimental design (one-group pretest-posttest). The sample consisted of 21 students. The average pretest score was 60.47, increasing to 82.85 after the treatment. A paired t-test showed that tcount = 13.35 > ttable = 2.086, indicating a significant influence. Thus, the NHT model effectively improves student cognitive achievement in Pancasila Education.